Empirical methods to estimate mechanical properties of jointed rock masses and a proposal for a geophysical method to assist geological discontinuity characterization - Polemis Júnior, Konstantinos (2019)
Rock engineering is the applied science related to human activities using the rock as an engineering material for different purposes, such as tunnels support, open-pit mine, underground excavation, mining shafts, among others. Its foundation lies in rock mechanics, which studies the mechanical behavior of this geomaterial in response to any change in the stress field of the rocks caused by the forces acting on them, taking into account the individual characteristics of the intact rock and the geological discontinuities within its medium. Because of the anisotropic and heterogeneous characteristics of the material, arising especially from the scale effect existing in jointed rock masses, estimating their mechanical properties can be seen as a complex and expensive task. As an alternative, empirical methods based on rock mass classification systems (RMCS), e.g., RMR, Q and GSI systems, have been widely used for rock engineering practice purposes, including for deriving the compressive strength, σcm, and deformation modulus of the material, Erm, especially for numerical modeling. Once there are a significant number of empirical methods suggested for this purpose, this study evaluated the most known correlations based on the RQD index, RMR number, Q-value, and GSI number, using 46 scenarios of different rock mass quality previously characterized and classified. As part of the results found, it was noticed that non-normalized correlations yielded overestimated values of deformation modulus in direct comparison to the normalized one, especially for better rock mass quality scenarios, where the difference was way more significative. This study also proposed the usage of a geophysical technique, the ground-penetrating radar (GPR), as an auxiliary survey tool for in situ rock mass characterization, for rock mass classification purposes. As a case of study, a comparative analysis between a geological mapping of discontinuities identified using an unmanned aerial vehicle (UAV) from an outcrop and the underground discontinuity imaging using the GPR was conducted in the Castanhão dam region. Based on the results derived after basic and advanced processing of the raw data collected in loco, it was confirmed the capacity of the geophysical method for mapping discontinuities with high resolution for rock mass characterization purposes.